Non-stationary seismic response of tanks with soil interaction by wavelets. - Chatterjee, Pranesh
A wavelet based random vibration theory has been developed for the non-stationary seismic response of liquid storage tanks including soil interaction. The ground motion process has been characterized via estimates of statistical functionals of wavelet coefficients obtained from a single time history of ground accelerations. The tank liquid soil system has been modelled as a two degree of freedom (2 DOF) system. The wavelet domain equations have been formulated and the wavelet coefficients of the required response state are obtained by solving two linear simulataneous algebraic equations. The explicit expression for the instantaneous power spectral density function (PSDF) in terms of the functionals of the input wavelet coefficients has been obtained. The moments of this PSDF are used to estimate the expected pseudo-spectral acceleration (PSA) response of the tank. Parametric variations are carried out to study the effects of tank height, foundation natural frequency, shear wave velocity of soil and ratio of the mass of tank (including liquid) to the mass of foundation on the PSA responses of tanks.
Keywords: Wavelet; Non-stationarity.; Tanks; Seismic excitation; Soil interaction